2000
DOI: 10.1016/s0002-9440(10)64950-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Hepatocyte Growth Factor (HGF) Receptor (Met) and Presence of a Truncated and Activated Intracellular HGF Receptor Fragment in Locally Aggressive/Malignant Human Musculoskeletal Tumors

Abstract: The hepatocyte growth factor (HGF) regulates biological functions such as cell growth, cell migration, and morphogenesis by activation of its tyrosine kinase receptor Met.1 The HGF receptor/Met is a 190-kd heterodimeric transmembrane receptor composed of a 50-kd ␣-and a 140-kd ␤-subunit. The ␤-subunit is a transmembrane spanning protein with an intracellular tyrosine kinase domain that can be activated by autophosphorylation of two tyrosine residues.2 Although the Hgfr/Met proto-oncogene was originally identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 29 publications
5
64
0
Order By: Relevance
“…Furthermore, it could even be used for studies of ErbB2 cleavage in transgene animals. Cleavage is also an important regulator of other proteins, e.g., ErbB4, Met, Notch, CD44, p75/NTR, and APP (Selkoe et al, 1996;Haass and De, 1999;Wallenius et al, 2000;Ni et al, 2001;Zampieri et al, 2005;Petrelli et al, 2006;Sugahara et al, 2006), and tandem fusion proteins made from these proteins similarly to YEC could be highly useful. An important advantage of such constructs is that one avoids the problems inherent to ratiometric studies based on immunofluorescence, namely availability of protein epitopes and steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could even be used for studies of ErbB2 cleavage in transgene animals. Cleavage is also an important regulator of other proteins, e.g., ErbB4, Met, Notch, CD44, p75/NTR, and APP (Selkoe et al, 1996;Haass and De, 1999;Wallenius et al, 2000;Ni et al, 2001;Zampieri et al, 2005;Petrelli et al, 2006;Sugahara et al, 2006), and tandem fusion proteins made from these proteins similarly to YEC could be highly useful. An important advantage of such constructs is that one avoids the problems inherent to ratiometric studies based on immunofluorescence, namely availability of protein epitopes and steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…Other receptor tyrosine kinases are expressed as truncated forms in malignant cells, but usually these aberrant proteins are constitutively active kinases in which the catalytic domain is freed by negative constraints present in the full-length receptor. [7][8][9] By contrast, the truncated c-Kit protein does not contain an ATP binding site and should be catalytically inactive. 5 Our laboratory has previously described that a mouse homologue of the truncated human c-Kit is physiologically expressed only in the postmeiotic haploid cells of the testis; 10 more recently we have detected human tr-Kit also in human mature spermatozoa, indicating a conserved role of this protein in gamete function (Paronetto MP, Geremia R, Rossi P, and Sette C, manuscript in preparation).…”
mentioning
confidence: 99%
“…We and other have shown that the MET oncogene is aberrantly overexpressed in approximately 80% of all subtypes of human osteosarcomas, (3)(4)(5)(6)(7)31) although it is almost not detectable in other mesenchyme-derived tumors, such as fibrosarcoma and chondrosarcoma, as well as in adult tissues of mesenchymal origin. (3)(4)(5)(6)(7) To study MET-induced transformation of cells derived from mesenchymal lineages, we overexpressed the MET oncogene in primary cultures of human bone-derived cells and obtained MET overexpressing osteosarcoma (MET-OS) clones.…”
Section: Resultsmentioning
confidence: 99%
“…(3)(4)(5)(6)(7) To study MET-induced transformation of cells derived from mesenchymal lineages, we overexpressed the MET oncogene in primary cultures of human bone-derived cells and obtained MET overexpressing osteosarcoma (MET-OS) clones. (26) As previously reported, the MET-OS clones originated from independent and multiple events of MET transgene integration into cultured cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation